Developmental milestones of the autonomic nervous system revealed via longitudinal monitoring of fetal heart rate variability - Schneider, Uwe; Bode, Franziska; Schmidt, Alexander; Nowack, Samuel; Rudolph, Anja; Doelcker, Eva-Maria; Schlattmann, Peter; Götz, Theresa; Hoyer, Dirk (PloS one, 2018)
Fetal heart rate variability (fHRV) of normal-to-normal (NN) beat intervals provides high-temporal resolution access to assess the functioning of the autonomic nervous system (ANS). To determine critical periods of fetal autonomic maturation. The developmental pace is hypothesized to change with gestational age (GA). Prospective longitudinal observational study. 60 healthy singleton fetuses were followed up by fetal magnetocardiographic heart rate monitoring 4-11 times (median 6) during the second half of gestation. FHRV parameters, accounting for differential aspects of the ANS, were studied applying linear mixed models over four predefined pregnancy segments of interest (SoI: <27; 27+0-31+0; 31+1-35+0; >35+1 weeks GA). Periods of fetal active sleep and quiescence were accounted for separately. Skewness of the NN interval distribution VLF/LF band power ratio and complexity describe a saturation function throughout the period of interest. A decreasing LF/HF ratio and an increase in pNN5 indicate a concurrent shift in sympathovagal balance. Fluctuation amplitude and parameters of short-term variability (RMSSD, HF band) mark a second acceleration towards term. In contrast, fetal quiescence is characterized by sequential, but low-margin transformations; ascending overall variability followed by an increase of complexity and superseded by fluctuation amplitude. An increase in sympathetic activation, connected with by a higher ability of parasympathetic modulation and baseline stabilization, is reached during the transition from the late 2nd into the early 3rd trimester. Pattern characteristics indicating fetal well-being saturate at 35 weeks GA. Pronounced fetal breathing efforts near-term mirror in fHRV as respiratory sinus arrhythmia.